2012
DOI: 10.1001/archgenpsychiatry.2011.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Mental Disorders in Early Adulthood and Later Psychiatric Hospital Admissions and Mortality in a Cohort Study of More Than 1 Million Men

Abstract: Context: Mental disorders have been associated with increased mortality, but the evidence is primarily based on hospital admissions for psychoses. The underlying mechanisms are unclear.Objectives: To investigate whether the risks of death associated with mental disorders diagnosed in young men are similar to those associated with admission for these disorders and to examine the role of confounding or mediating factors.Design: Prospective cohort study in which mental disorders were assessed by psychiatric inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 34 publications
3
39
1
2
Order By: Relevance
“…However, milder and self-reported mental symptoms are prevalent also among employed people, with repercussions on their functioning, work ability and even mortality [4]. In our study, all-cause mortality, after considering covariates, showed no associations with either prior GHQ or MCS.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, milder and self-reported mental symptoms are prevalent also among employed people, with repercussions on their functioning, work ability and even mortality [4]. In our study, all-cause mortality, after considering covariates, showed no associations with either prior GHQ or MCS.…”
Section: Discussioncontrasting
confidence: 55%
“…It is estimated that people with mental disorders may lose 10 years of potential life, and that up to 14 % of deaths worldwide, i.e. each year eight million deaths, involve people with mental disorders [3, 4]. Such excess mortality risk concerns those with severe and diagnosed mental disorders, including schizophrenia, bipolar disorder, major depression and psychoses [3].…”
Section: Introductionmentioning
confidence: 99%
“…While large epidemiologic studies have examined mortality among persons with mental illness [18][19][20][21][22][23][24][25] and smaller studies have examined tobacco-related deaths among persons with substance abuse problems, [33][34] this is the first study of tobacco-related deaths among persons with mental health or substance abuse problems using population based data and including a general population comparison. First, as compared to the general population, tobacco-related deaths are much higher among persons who recently received substance abuse services alone or in combination with mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…BD is a chronic disease associated with high morbidity and mortality (Gale et al, 2012). Childhood-onset BD tends to be particularly severe and debilitating (Geller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%